DYNAMICS OF HUMAN RESOURCE MANAGEMENT AND THEIR IMPLICATIONS FOR THE PERSONAL COMPETENCIES OF EARLY CHILDHOOD EDUCATION TEACHERS - Nurul Wilantika; Subaidi Subaidi; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
Teacher personality competence is a crucial variable in Early Childhood Education (ECE) because children learn through the process of imitating role models. However, in practice, the development of this competence is often neglected compared to pedagogical and professional aspects. This study aims to analyze the urgency of ECE teacher personality competence from the perspective of Islamic Education Management (IEM) and to formulate a comprehensive Human Resource Management (HRM) strategy for its reinforcement. The method used is library research with a qualitative descriptive approach and content analysis techniques. The result show that teacher personality competence is the main foundation of character education, reflecting the traits of shiddiq, Amanah, tabligh and fathonah. Effective HRM strategies must include character-based recruitment using Behavioral Event Interview (BEI), mental spiritual development through mentoring and coaching, and performance appraisal systems that monitor the consistency of role modelling and teacher mental health. The conclusion of this study confirms that the integration of modern management with Islamic values creates an ecosystem that supports teachers in becoming uswatun hasanah for early childhood.